Toward a Holistic Model of Higher-Order Thinking Assessment in Islamic Environmental Education: Integrating Authentic Assessment, Moral Reasoning, and Sustainability - Abd. Aziz Rekan; Mohd Istajib Mokhtar; Muhamad Nasir Mohamad Salleh; M. Agung Rokhimawan; Muchammadun Muchammadun (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
The integration of Higher-Order Thinking Skills (HOTS) into Islamic education has become increasingly important in preparing learners to address complex environmental challenges through critical inquiry and ethical responsibility. Nevertheless, empirical evidence explaining how classroom assessment simultaneously cultivates higher-order thinking, moral reasoning, and sustainable behaviour remains limited. Consequently, this qualitative case study investigates how Islamic Education teachers implement HOTS assessment through the integration of environmental education in Malaysian secondary schools. Data were collected from three purposively selected teachers using semi-structured interviews, classroom observations, and document analysis, including lesson plans, students’ work, and school-based assessment records. Furthermore, the data were analysed thematically following the procedures of Miles, Huberman, and Saldaña. The findings reveal that HOTS assessment extends beyond merely measuring cognitive achievement by functioning as a holistic pedagogical process. It integrates authentic assessment, Islamic environmental ethics, and continuous classroom evaluation. Teachers employed oral questioning, contextualised written tasks, and behavioural observation to promote students’ abilities to analyse environmental problems, evaluate alternative solutions, reflect on Islamic values, and demonstrate responsible environmental practices. Based on these findings, the study proposes a conceptual model linking authentic HOTS assessment with higher-order thinking, moral reasoning, environmental stewardship, and responsible behavior. This model not only advances scholarship in Islamic education but also provides a theoretically grounded framework that connects holistic Islamic pedagogy with Education for Sustainable Development. Moreover, it offers practical guidance for designing value-based assessment in contemporary classrooms, thereby potentially enriching instructional strategies and fostering meaningful student engagement with environmental concerns.